Bedfordshire churches in the nineteenth century. - Pickford, Chris (Publications of the Bedfordshire Historical Record Society, 1994)
The first in a series of three volumes describing Bedfordshire's parish churches in detail, this book will appeal to anyone interested in old churches. Based on original sources, the book also contains a commentary on each church and explanatory footnotes to the sources. It is illustrated with contemporary watercolors, engravings and photographs - many of them now published for the first time. Adding much new material to previously published accounts, it will be an invaluable aid to future researchers and compilers of guide books.